Comparative Analysis of Brand Image between Lining and Victor Shoes Among Badminton Players in Gelanggang Remaja Koja, Jakarta - Natalia, Desy Uli (CV. Lenggogeni Data Publishing, 2023)
In playing badminton, one of the supporting facilities used is badminton shoes (Fitantri, 2015). As well as protecting the feet, shoes can also prevent injury and acceleration when on the field. A common phenomenon related to brand image that usually appears is the feeling or impression that consumers get after using a brand. This study aims to determine the difference between the brand image of Lining shoes and Victor shoes according to Badminton players at the Koja Youth Center in Jakarta. The method used is a quantitative method with a comparative research type. The population in this study were all badminton players at the Koja Jakarta Youth Center, totaling 60 people. The research was conducted at the Koja Jakarta Youth Center in selecting the sample using a purposive sampling technique. Then, for data analysis used descriptive analysis and Paired T-Test. Based on the results of the Paired T-Test, the mean value of Lining's shoe brand image was 47.1500, then the mean value of Victor's shoe brand image was 51.8333. This shows that the brand image of Victor shoes is higher or better than the brand image of Lining shoes based on the results of research on 60 users of Lining shoes and Victor shoes who are badminton players at the Koja Youth Center in Jakarta. Dalam bermain bulu tangkis sarana pendukung yang dipergunakan salah satunya adalah sepatu bulu tangkis (Fitantri, 2015). Selain sebagai pelindung kaki, sepatu juga dapat menghindari cedera dan percepatan pada saat di lapangan. Fenomena umum terkait brand image yang biasanya muncul yaitu perasaan atau kesan yang diperoleh konsumen setelah menggunakan suatu merek. Penelitian ini bertujuan untuk untuk mengetahui perbedaan antara brand image sepatu Lining dan sepatu Victor menurut pemain Badminton di Gelanggang Remaja Koja Jakarta. Metode yang digunakan adalah metode kuantitatif dengan jenis penelitian berupa komparatif. Populasi dalam penelitian ini adalah seluruh pemain badminton yang di Gelanggang Remaja Koja Jakarta yang berjumlah 60 orang. Penelitian yang dilakukan di Gelanggang Remaja Koja Jakarta dalam pemilihan sampel menggunakan teknik purposive sampling. Kemudian, untuk analisis data digunakan analisis deskriptif dan Uji Paired T-Test. Berdasarkan hasil uji Paired T-Test nilai mean brand image sepatu Lining yaitu 47,1500 kemudian nilai mean brand image sepatu Victor yaitu 51,8333. Hal ini menunjukkan bahwa brand image sepatu Victor lebih tinggi atau lebih baik daripada brand image sepatu Lining berdasarkan hasil penelitian kepada 60 orang pengguna sepatu Lining dan sepatu Victor yang merupakan pemain badminton di Gelanggang Remaja Koja Jakarta. Kata Kunci: Brand Image, Lining, Victor